Evaluation of a retrospective diary for peri‐conceptual and mid‐pregnancy drinking in Scotland: a cross‐sectional study. (3rd December 2016) - Symon, Andrew; Rankin, Jean; Butcher, Geraldine; Smith, Lesley; Cochrane, Lynda
Abstract: Introduction: Heavy episodic ("binge") drinking among women in Scotland is commonplace; prepregnancy drinking is associated with continued antenatal drinking. Evidence for effectiveness of standardized antenatal alcohol assessment is lacking. Alcohol‐exposed pregnancies may be missed. We assessed peri‐conceptual and mid‐pregnancy consumption using a week‐long retrospective diary and standard alcohol questionnaires, and evaluated the agreement between these instruments. Material and methods: Cross‐sectional study in two Scottish health board areas involving 510 women attending mid‐pregnancy ultrasound scan clinics. Face‐to‐face administration of alcohol retrospective diary and AUDIT or AUDIT‐C assessed weekly and daily alcohol consumption levels and patterns. Depression‐Anxiety‐Stress Scale (DASS‐21) assessed maternal wellbeing. A sub‐sample ( n  = 30) provided hair for alcohol metabolite analysis. Pearson's correlation coefficient investigated associations between questionnaires and alcohol metabolite data. Results: The response rate was 73.8%. The retrospective diary correlated moderately with AUDIT‐C and AUDIT but elicited reports of significantly higher peri‐conceptual consumption, (median unit consumption on "drinking days" 6.8; range 0.4–63.8). Additional "special occasions" consumption ranged from 1 to 125 units per week. Correlations between DASS‐21 and retrospective diary were weak. Biomarker analysis identified three instances of hazardous peri‐conceptual drinking. Conclusions: Women reported higher consumption levels when completing the retrospective diary, especially regarding peri‐conceptual "binge" drinking. Routine clinical practice methods may not capture potentially harmful or irregular drinking patterns. Given the association between prepregnancy and antenatal drinking, and alcohol's known teratogenic effects, particularly in the first trimester, the retrospective diary may be a useful low‐tech tool to gather information on alcohol intake patterns and levels.